1999
DOI: 10.1542/peds.103.6.1253
|View full text |Cite
|
Sign up to set email alerts
|

Language Barriers and Resource Utilization in a Pediatric Emergency Department

Abstract: Despite controlling for multiple factors, the presence of a physician-family LB was associated with a higher rate of resource utilization for diagnostic studies and increased ED visit times. Additional study is recommended to explore the reasons for these differences and ways to provide care more efficiently to non-English-speaking patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 269 publications
(153 citation statements)
references
References 16 publications
4
146
1
2
Order By: Relevance
“…Several studies have demonstrated that patients with little or no English skills are at risk of experiencing a barrier to health care in the United States such as poor compliance with primary prevention, medical treatment, and follow-up services (6). Language barriers are associated with increased testing, increased ED lengths of stay, and higher hospital admission rates (1)(2)(3). Consistent with prior literature, language discordance was the most common form of CB encountered in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Several studies have demonstrated that patients with little or no English skills are at risk of experiencing a barrier to health care in the United States such as poor compliance with primary prevention, medical treatment, and follow-up services (6). Language barriers are associated with increased testing, increased ED lengths of stay, and higher hospital admission rates (1)(2)(3). Consistent with prior literature, language discordance was the most common form of CB encountered in our study.…”
Section: Discussionsupporting
confidence: 86%
“…There is limited research addressing the effect of language barriers on diagnostic test utilization, ED length of stay, and hospital admission (1)(2)(3). We were unable to find studies that directly examine the effect of communication barriers (CBs) on the diagnostic power of the medical interview.…”
Section: Introductionmentioning
confidence: 99%
“…2 English proficiency in the Hispanic population is important to consider when evaluating health outcomes and disparities because US health care delivery is provided largely by monolingual English speakers. [3][4][5] Asthma serves as a good model for exploring the effect of language barriers on the health of Hispanic persons. Asthma is the most common chronic illness among children, and documented disparities exist between racial/ ethnic groups.…”
mentioning
confidence: 99%
“…In situations where parents are non-English speaking, it has become common for children, friends, or unofficial healthcare providers (eg, nurses or social workers) to be used as interpreters. The information that must be interpreted may be beyond not only the children's comprehension, but also that of the untrained ad hoc interpreter [26,27] In 1999, it was noted that despite controlling for multiple factors, the presence of a physician-family language barrier was associated with use of more resources for diagnostic studies and also increased emergency department visit times [27]. In pediatrics, failure to culturally and linguistically communicate effectively can result in multiple adverse consequences including difficulties with informed consent, inadequate understanding of diagnoses and treatment by families, dissatisfaction with care, preventable complications or death, unnecessary child maltreatment evaluations, clinician bias, and ethnic confusion with respect to disparities in prescriptions, analgesia, test ordering, and diagnostic evaluations [28].…”
Section: Use Of Interpreters For Childrenmentioning
confidence: 99%